Aktivitas Hepatoprotektor Ekstrak Metanol Akar Pasak Bumi dan Fraksi-Fraksi Turunannya - Ruqiah Ganda Putri Panjaitan; Wasmen Manalu; Ekowati Handharyani; Chairul - (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2011)
The hepatoprotector activity of pasak bumi (Eurycoma longifolia Jack.) roots was evaluated in carbontetrachloride (CCl4)-induced rats. Each rat was administered 500 mg/kg body weight of metanol extractand its derivates (n-hexane, chloroform, ethyl acetate, and methanol-water) for 7 consecutive days. Thepositive control group received 25 mg silymarin/kg body weight daily for 7 consecutive days. Hepatoprotectoractivity was assessed by measuring serum alanine transaminase (ALT) and aspartate transaminase(AST). Futhermore, hepatic tissues were subjected to histopathological studies. The results and AST(272.33±85.63 U/L) compared to methanol extract (380.61±324.88 U/L and 475.27±412.31 U/L), n-hexanefraction (279.80±304.92 U/L and 488.53±426.81 U/L), chloroform fraction (418.30±294.80 U/L and427.70±273.08 U/L), and ethyl acetate fraction (312.80±443.30 U/L and 418.40±370.52 U/L), but thisresult was not as good as silymarin (ALT 105.09±21.62 U/L and AST 310.25±2.45 U/L). Moreover, thehistopathological studies of methanol-water fraction was also not as good as silymarin . It was concludedthat methanol-water fraction of pasak bumi roots has a hepatoprotector potensial.